Cervical Lymph Node Metastasis in Adenoid Cystic Carcinoma of the Larynx: A Collective International Review. Issue 4 (April 2016) - Coca-Pelaz, Andrés; Barnes, Leon; Rinaldo, Alessandra; Cardesa, Antonio; Shah, Jatin; Rodrigo, Juan; Suárez, Carlos; Eloy, Jean; Bishop, Justin; Devaney, Kenneth; Thompson, Lester; Wenig, Bruce; et al.
Abstract Adenoid cystic carcinoma (AdCC) of the head and neck is a well-recognized pathologic entity that rarely occurs in the larynx. Although the 5-year locoregional control rates are high, distant metastasis has a tendency to appear more than 5 years post treatment. Because AdCC of the larynx is uncommon, it is difficult to standardize a treatment protocol. One of the controversial points is the decision whether or not to perform an elective neck dissection on these patients. Because there is contradictory information about this issue, we have critically reviewed the literature from 1912 to 2015 on all reported cases of AdCC of the larynx in order to clarify this issue. During the most recent period of our review (1991–2015) with a more exact diagnosis of the tumor histology, 142 cases were observed of AdCC of the larynx, of which 91 patients had data pertaining to lymph node status. Eleven of the 91 patients (12.1%) had nodal metastasis and, based on this low proportion of patients, routine elective neck dissection is therefore not recommended.